An evaluation of two large scale demand side financing programs for maternal health in India: the MATIND study protocol - Sidney Kristi; de Costa Ayesha; Diwan Vishal; Mavalankar Dileep V; Smith Helen (BMC, 2012)
Abstract Background High maternal mortality in India is a serious public health challenge. Demand side financing interventions have emerged as a strategy to promote access to emergency obstetric care. Two such state run programs, Janani Suraksha Yojana (JSY)and Chiranjeevi Yojana (CY), were designed and implemented to reduce financial access barriers that preclude women from obtaining emergency obstetric care. JSY, a conditional cash transfer, awards money directly to a woman who delivers in a public health facility. This will be studied in Madhya Pradesh province. CY, a voucher based program, empanels private obstetricians in Gujarat province, who are reimbursed by the government to perform deliveries of socioeconomically disadvantaged women. The programs have been in operation for the last seven years. Methods/designs The study outlined in this protocol will assess and compare the influence of the two programs on various aspects of maternal health care including trends in program uptake, institutional delivery rates, maternal and neonatal outcomes, quality of care, experiences of service providers and users, and cost effectiveness. The study will collect primary data using a combination of qualitative and quantitative methods, including facility level questionnaires, observations, a population based survey, in-depth interviews, and focus group discussions. Primary data will be collected in three districts of each province. The research will take place at three levels: the state health departments, obstetric facilities in the districts and among recently delivered mothers in the community. Discussion The protocol is a comprehensive assessment of the performance and impact of the programs and an economic analysis. It will fill existing evidence gaps in the scientific literature including access and quality to services, utilization, coverage and impact. The implementation of the protocol will also generate evidence to facilitate decision making among policy makers and program managers who currently work with or are planning similar programs in different contexts.